2012
DOI: 10.1007/s12185-012-1139-1
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of pandemic 2009 influenza A/H1N1 infection in the hematology ward: fatal clinical outcome of hematopoietic stem cell transplant recipients and emergence of the H275Y neuraminidase mutation

Abstract: We report an outbreak of pandemic 2009 influenza A/H1N1 virus (2009 H1N1) infection that occurred in the hematology ward of our institution during the 2010-2011 influenza season. A total of seven hospitalized patients with hematologic tumors, including five recipients of hematopoietic stem cell transplantation (HSCT), successively developed rapid influenza detection test (RIDT)-positive influenza A; four patients had laboratory-confirmed 2009 H1N1 infection. Three HSCT recipients required mechanical ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…, who noted that increased mortality may occur with nosocomial acquisition. Iloka and colleagues also reported 3 deaths in 5 HSCT recipients who acquired infection nosocomially. Patients with nosocomial infection may have a greater mortality, as they are likely to have other co‐morbidities that lead to an overall greater burden of illness.…”
Section: Discussionmentioning
confidence: 98%
“…, who noted that increased mortality may occur with nosocomial acquisition. Iloka and colleagues also reported 3 deaths in 5 HSCT recipients who acquired infection nosocomially. Patients with nosocomial infection may have a greater mortality, as they are likely to have other co‐morbidities that lead to an overall greater burden of illness.…”
Section: Discussionmentioning
confidence: 98%
“…These antibodies can be used for prophylactic and therapeutic treatments of influenza virus infections. Although the large amount of MAb needed for treatment might preclude the use of the antibodies in the general population, this approach might be useful for the therapy of severe influenza cases, especially when drug-resistant viruses in an immunocompromised host are involved (57)(58)(59)(60)(61)(62)(63). We therefore wanted to evaluate MAb 6F12 in a prophylactic setting in the ferret model.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the rate of oseltamivir resistance is much higher among high-risk groups such as immunocompromised patients, and clusters of high community transmission rates have been reported [25,27]. Hurt et al [28] reported a significant increase in the frequency H275Y oseltamivir-resistant H1N1p viruses in a community in Australia.…”
Section: Discussionmentioning
confidence: 99%